Unicompartmental Knee Arthroplasty: Factors Influencing the Outcome - Xing, Zhiqing; Katz, Jonathan; Jiranek, William (The Journal of Knee Surgery, 2012)
Currently, the outcome and indications of unicompartmental knee arthroplasty (UKA) are still controversial. We retrospectively reviewed a consecutive case series of UKA done by a single surgeon between 2004 and 2007 including 178 knees (140 patients). There were 31 lateral UKA and 147 medial UKA. With a minimum follow-up of 24 months (average 54 months) in 159 knees (other 19 knees were lost to follow-up at 3 to 18 months after surgery), 6 knees (3.8%, all medial UKA) were converted to total knee arthroplasty in 17 to 66 months (average 33 months). We found that the outcome of UKA was not influenced by the patient's age, body mass index, or early degeneration in the patellofemoral joint (PFJ). Compared with other reports, there was a greater proportion of lateral UKA in our series (17.4%). Although lateral UKA showed a trend toward less complications and implant failure compared with medial UKA, WOMAC scores (Western Ontario and McMaster Universities Osteoarthritis Index) were similar between the two types of partial knee arthroplasty. Our results indicate that young age, obesity, and early degeneration in the PFJ may not be contraindications to UKA, and lateral UKA functions as well as, if not better than medial UKA. However, a long-term follow-up is required to confirm these findings.
Keywords: unicompartmental; knee; arthroplasty; incidence; outcome